2005
DOI: 10.1152/ajpendo.00413.2004
|View full text |Cite
|
Sign up to set email alerts
|

Combined ingestion of protein and free leucine with carbohydrate increases postexercise muscle protein synthesis in vivo in male subjects

Abstract: The present study was designed to determine postexercise muscle protein synthesis and whole body protein balance following the combined ingestion of carbohydrate with or without protein and/or free leucine. Eight male subjects were randomly assigned to three trials in which they consumed drinks containing either carbohydrate (CHO), carbohydrate and protein (CHO+PRO), or carbohydrate, protein, and free leucine (CHO+PRO+Leu) following 45 min of resistance exercise. A primed, continuous infusion of L-[ring-13C6]p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
197
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(224 citation statements)
references
References 49 publications
22
197
0
5
Order By: Relevance
“…In fact, protein synthesis rates were additive for the carbohydrate and amino acids supplement compared with the carbohydrate-only and amino acids-only supplements. Levenhagen et al (20) and Koopman et al (15) observed similar results. Following a 60-minute bout of cycling exercise, Levenhagen et al (20) provided subjects with placebo, a CHO supplement, or a CHO-PRO supplement.…”
Section: File # 84tqmentioning
confidence: 53%
See 1 more Smart Citation
“…In fact, protein synthesis rates were additive for the carbohydrate and amino acids supplement compared with the carbohydrate-only and amino acids-only supplements. Levenhagen et al (20) and Koopman et al (15) observed similar results. Following a 60-minute bout of cycling exercise, Levenhagen et al (20) provided subjects with placebo, a CHO supplement, or a CHO-PRO supplement.…”
Section: File # 84tqmentioning
confidence: 53%
“…Leg protein synthesis rates following CHO-PRO supplementation improved 600% compared with placebo and 400% compared with CHO-only supplementation. Koopman et al (15) were able to demonstrate a significantly reduced whole body protein breakdown and a significantly increased whole body protein synthesis by feeding subjects a CHO-PRO or CHO-PRO-leucine supplement in comparison to providing a CHO-only supplement following a resistance exercise bout. Furthermore, van Loon et al (34) found a significant negative correlation between the insulin response and plasma levels of select amino acids after subjects cycled for ϳ90 minutes of interval-based activity and were fed CHO-only or CHO-PRO supplements postexercise.…”
Section: File # 84tqmentioning
confidence: 99%
“…These data are supported by the observation that leucine increased protein synthesis in pregnant tumour-bearing rats, possibly resulting from changes in the ubiquitin -proteasome system (Ventrucci et al, 2004). In humans, leucine supplementation resulted in an improved muscle protein synthesis in young (Koopman et al, 2005) and elderly volunteers (Katsanos et al, 2006;Koopman et al, 2006;Rieu et al, 2006). There are two clinical trials in cancer patients that studied oral BCAA supplementation after surgical removal of the tumour.…”
mentioning
confidence: 85%
“…Esse fato é relevante, uma vez que a ingestão de leucina aumenta a fosforilação de proteínas envolvidas na regulação da síntese protéica muscular, incluindo a p70 S6k (Figura 3) Kimball, Jefferson, 2006a;Norton, Layman, 2006;Anthony et al, 2000). Koopman et al (2005) verificaram que a adição de leucina em bebida contendo hidrolisado protéico e carboidratos promoveu maior estimulação da síntese protéica corporal total após a realização de uma sessão de exercício de força quando comparada à ingestão de carboidrato ou de carboidrato com hidrolisado protéico. Além disso, a ingestão combinada de carboidrato, hidrolisado protéico e leucina aumentou a síntese protéica muscular em relação à ingestão isolada de carboidrato.…”
Section: Exercício De Força Balanço Protéico Muscular E Aminoácidosunclassified